VISIT-TO-VISIT BLOOD PRESSURE VARIABILITY IS ASSOCIATED WITH RISK OF HOSPITALIZATION IN A COMMUNITY ELDERLY COHORT OF 1095 PARTICIPANTS IN HONG KONG. (April 2021) - Yiu, Karen; Tsoi, Kelvin; Yu, Ruby; Woo, Jean; Lee, Eric; Wong, Samuel
Abstract : Objective: Hospitalization rate is significantly higher among the elderly compared to those aged below 65. This study aimed to identify the risk factors to predict the hospitalization based on the visit-to-visit BPV. Design and method: e-Health project is an ongoing multi-centered programme targets to monitor BP in the elderly community by using cloud system for real-time analysis. Participants had regular BP measurement weekly and those with at least 30 BP records in the first year of follow-up were included in this analysis. Visit-to-visit BPV is defined by the mean absolute residuals of individual linear regression trend of BP readings. Machine learning approach has been used to stratify the levels of BPV for K-means clustering algorithm on both systolic and diastolic BP. All subjects were classified into low, medium and high levels of BPV groups. The hospitalization was used as the study outcome. Age, gender, mean BP, BPV, number of medications used, frailty, sarcopenia, and memory function were considered to investigate the associations. Multivariate logistic regression was used to measure the odds ratio (OR) with 95% confidence interval (CI). Results: A total of 1, 095 subjects were follow-up for 1 year with average of 163 BP readings per each participant (SD = 74). Age, BPV, use of medications, frailty, sarcopenia, and memory function were shown to be associated with the risk of hospitalization (Table 1). In the multivariate analyses, there were significantly increased risk of hospitalization in the medium and high BPV groups (OR = 1.67; 95% CI = 1.23–2.28 and OR = 2.07; 95% CI = 1.36–3.13, respectively), in patients prescribed 1–4 medications and 5 or above medications (OR = 2.39; 95% CI = 1.29–4.86 and OR = 4.05; 95% CI = 2.09–8.51, respectively); in the pre-frail and frail groups (OR = 1.47; 95% CI = 1.04–2.09 and OR = 3.15; 95% CI = 2.11–4.74, respectively). Figure. No caption available. Conclusions: Visit-to-visit BPV, other than comorbid conditions with complex medication used and personal frailty, is shown to be a risk factor for hospitalization. Regular measurement of blood pressure is recommended to better understand BPV levels.